(untitled) (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Online shopping has become one of the inevitable things in human activities because of its effectiveness. Online shopping makes it easy for buyers to make transactions anytime and anywhere. Online shopping also supports sellers’ marketing activities because it becomes more effective even without a physical store. TikTok is one of several online platforms where people can do online shopping. With a large number of online shop owners using the TikTok platform, language variation will emerge. This study focuses on registers used in live streaming on TikTok, and there is not much research that examines this online platform. This study is expected can enrich and develop knowledge regarding registers used in online platforms. Register is the language of a person or group shares, interests, occupation, or language used in certain situations related to the group. There are five types of registers which are frozen or oratorical, formal or deliberative, consultative, casual, and intimate. This study uses qualitative research with the source of data from two online sellers who are doing a live to sell their product. The data used are utterances produced by those two online sellers. The result shows that there are three types of registers used in TikTok Live and two others are not.